Singing the King's Death: Voice and Sound in 1715. Issue 1 (2nd January 2019) - Hammond, Nicholas
Abstract : The central thesis of this article is that Louis XIV's reign, which has tended to be considered from an exclusively visual perspective, warrants re-evaluation from a sonic angle. Voice and sound assume a particular intensity at the time of the king's final illness and after his death in 1715: not only do those closest to Louis, including Mme de Maintenon and his two servants, the Antoine brothers, take care to record the monarch's final words and the sound of his voice, but the voices of others commemorate and question the legacy of a king who in his later years presided over military defeats, crippling taxes and widespread hardship. The words of preachers, such as Quiqueran de Beaujeu and Massillon, take inspiration from criticism of the monarch on the street, just as the thriving song culture around the Pont-Neuf gives a socially diverse populace the opportunity to hear about the king's funeral and to express different responses to their king's demise. Web-links to performances of the songs onhttp://parisiansoundscapes.org give readers the chance to listen to the sound of songs which until now have only been considered for their textual content.